2003
DOI: 10.2527/2003.8161517x
|View full text |Cite
|
Sign up to set email alerts
|

Parturition body size and body protein loss during lactation influence performance during lactation and ovarian function at weaning in first-parity sows1

Abstract: We investigated the effect of body protein mass at parturition and different degrees of body protein loss in lactation on sow performance. In a 2 x 2 factorial arrangement, 77 Genex gilts were fed to achieve either a standard or high body mass at parturition and to lose either a moderate (MPL) or high (HPL) amount of protein in lactation. Pregnant gilts were fed either 24.4 MJ of ME, 266 g of CP, and 11 g of lysine/d or 34.0 MJ of ME, 436 g of CP, and 20 g of lysine/d resulting in divergent (P < 0.01) live wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
65
1
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 40 publications
12
65
1
6
Order By: Relevance
“…The detrimental effect of protein restriction has already been reported on ovulation rate at the first estrus after weaning [10]. It is also consistent with data showing an impaired folliculogenesis at or after weaning in sows that lost a high amount of body protein during lactation compared with sows that lost a moderate amount of protein [11,35,36]. Such impairment was illustrated by a lower proportion of large follicles and reduced concentrations of oestradiol and/or IGF-I in follicular fluid.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The detrimental effect of protein restriction has already been reported on ovulation rate at the first estrus after weaning [10]. It is also consistent with data showing an impaired folliculogenesis at or after weaning in sows that lost a high amount of body protein during lactation compared with sows that lost a moderate amount of protein [11,35,36]. Such impairment was illustrated by a lower proportion of large follicles and reduced concentrations of oestradiol and/or IGF-I in follicular fluid.…”
Section: Discussionsupporting
confidence: 79%
“…Such impairment was illustrated by a lower proportion of large follicles and reduced concentrations of oestradiol and/or IGF-I in follicular fluid. Clowes et al [11] also reported that the sow's body mass at parturition has a greater effect on ovarian characteristics than protein loss during lactation. This was in agreement with the fact that heavy sows in the present experiment were less affected by protein loss than light sows, concerning ovulation rate.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Sows under severe catabolism present reduced IGF-1 levels (Patterson et al, 2011), inducing the mobilization of endogenous protein (Zak et al, 1997). Protein mass losses >12% during lactation may reduce follicle number and diameter, and decrease IGF-1 levels in sows submitted to dietary protein restriction during lactation (Clowes et al, 2003a and2003b). Schenkel et al (2010) recently reported reduced size of the next litter when sow's body mass and protein mass losses exceeded 8% and 9%, respectively.…”
Section: Discussionmentioning
confidence: 99%